GEOSTATISTICAL ANALYSIS FOR SPATIAL EVALUATION OF LIQUEFACTION POTENTIAL IN SAITAMA CITY - Rama Mohan Pokhrel; Jiro Kuwano; Shinya Tachibana (International Association of Lowland Technology, 2012)
The liquefaction potential (PL) values within the sedimentary basins are variable within short distances. If PL value does not exist quantitatively at a location of interest then data collected at other locations must be used to estimate the value for the desired locations. The aim of this study is the application of geostatistical method using randomly distributed measured liquefaction potential data to estimate more reliable PL value where measured data is not available. An experimental semivariogram was constructed from these randomly distributed measured locations to characterize the spatial variability of the measured PL value. A model semivariogram curve for isotropic and anisotropic modeling was fitted for the experimental curve to estimate the PL value for the unsampled locations. Using these model curves the potential value for the unsampled locations was estimated. To check the validity of the method and better model the estimated PL value was correlated with the measured PL value at the same locations. The greater R2 value given by the anisotropic model shows the benifit of anisotropic modeling in liquefaction potential mapping.